Evaluación técnico financiera del uso de la tecnología selex asp para el mejoramiento del proceso de transporte del crudo Castilla por un tramo del oleoducto Apiay - Porvenir (2017)
Precipitation of asphaltenes and other metals during Crudo transport processes has been predominantly the cause of the lack of development of areas containing heavy hydrocarbon deposits and which also exhibit excessive viscosities and low API gravity; in consequence; Over the years, efforts have been made to advance in different techniques; In order to ensure the flow of the fluid through the pipelines constructed, to avoid wastage of time and money associated with said inconvenience, which causes inter alia, the need for strict control of pump temperatures at dispatch and receipt stations and for And second, the frequency of pressure losses caused by the reduction of the effective diameter of the pipe. This study proposes, as main object, to make a comparison of the behavior of Crude Castile; Exploited in the Llanos Basin, before and after the application of an up grade technology; Which separates heavier molecules from crude oil and in particular asphaltene molecules through a pre-refining process by handling a fluid such as n-pentane and as a result of a technical process without major difficulties.